What Role Can Open Science Play in Enabling South-North Dialogues? - Havemann, Johanna; Ahinon, Justin, Sègbédji (My University, 2019)
This presentation was held at the 14th eLearning Africa Conference in Abidjan, Cote d'Ivoire. HEI10 Thursday, 24 October 2019 14:30 – 15:30 Room: Daloa Description: Participants of this Knowledge Exchange Session will learn how an open repository specific for the African research community can trigger interdisciplinary research within the continent as well as globally, with research institutions overseas. The aim of this platform is to provide more visibility and more opportunities to African scientists.
Keywords: open access; open science; preprint; research in africa